2018
DOI: 10.3892/ol.2018.8561
|View full text |Cite
|
Sign up to set email alerts
|

Mps1 is associated with the BRAFV600E mutation but does not rely on the classic RAS/RAF/MEK/ERK signaling pathway in thyroid carcinoma

Abstract: Abstract.In previous studies, the B-Raf proto-oncogene, serine/threonine kinase (BRAF) V600E mutation has been identified in multiple malignant tumors. BRAF V600E has been revealed to contribute to tumorigenesis by the activation of phospho-mitogen-activated protein kinases (MAPKs) and their downstream Monopolar spindle 1 (Mps1), leading to chromosome euploidy and tumor development. In the present study, the presence of phospho-MAPK and Mps1 in 161 thyroid carcinoma cases with complete clinical parameters was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…SIRT6 was most positively associated with LSM7 and FKBP8 but most negatively associated with STT3B and CLCN3 while genes most positively associated with SIRT7 were SPSB3 , ZGPAT , PUS1 , and TSEN54 but PRKAR2A and PDZD8 were the most negatively associated with SIRT7 (Figures 5 and 6 ). Specially, BRAF mutation is the most common gene alteration in DTC [ 30 ]. We examined the correlation between SIRTs and BRAF and found that BRAF was positively associated with SIRT1 , SIRT2 , SIRT3 , SIRT4 , SIRT5 , and 7 but negatively associated with SIRT6 ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…SIRT6 was most positively associated with LSM7 and FKBP8 but most negatively associated with STT3B and CLCN3 while genes most positively associated with SIRT7 were SPSB3 , ZGPAT , PUS1 , and TSEN54 but PRKAR2A and PDZD8 were the most negatively associated with SIRT7 (Figures 5 and 6 ). Specially, BRAF mutation is the most common gene alteration in DTC [ 30 ]. We examined the correlation between SIRTs and BRAF and found that BRAF was positively associated with SIRT1 , SIRT2 , SIRT3 , SIRT4 , SIRT5 , and 7 but negatively associated with SIRT6 ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In human cancers, aberrant activation of the RAF/MEK/ERK signaling pathway is frequently observed. There has been increasing evidence revealing the importance of the RAF/MEK/ERK signaling pathway in tumorigenesis (6567). The relatively high frequency of activating mutations of RAS (~20% of all human types of cancer), an upstream activator of the well-established RAF/MEK/ERK signaling cascade, as well as frequent activating mutations in the BRAF kinase gene (~7% of all human types of cancer) have been observed (68).…”
Section: Discussionmentioning
confidence: 99%